Suppression of Serum Interferon‐γ Levels as a Potential Measure of Response to Ustekinumab Treatment in Patients With Systemic Lupus Erythematosus. Issue 3 (1st February 2021) - Cesaroni, Matteo; Seridi, Loqmane; Loza, Matthew J.; Schreiter, Jessica; Sweet, Kristen; Franks, Carol; Ma, Keying; Orillion, Ashley; Campbell, Kim; M. Gordon, Robert; Branigan, Patrick; Lipsky, Peter; et al.
Abstract : Objective: In a previously reported phase II randomized, placebo‐controlled, interventional trial, we demonstrated that treatment with ustekinumab, an anti–interleukin‐12 (IL‐12)/IL‐23 p40 neutralizing monoclonal antibody, improved global and organ‐specific measures of disease activity in patients with active systemic lupus erythematosus (SLE). Utilizing the biomarker data from this phase II clinical study, we sought to determine whether modulation of the expression of IL‐12, IL‐23, or both cytokines by ustekinumab is associated with clinical efficacy in patients with SLE. Methods: This phase II randomized, placebo‐controlled study enrolled 102 patients with autoantibody‐positive SLE whose disease remained active despite standard‐of‐care therapy. Patients were randomized at a 3:2 ratio to receive 6 mg/kg ustekinumab intravenously or placebo at week 0, followed by subcutaneous injections of 90 mg ustekinumab or placebo every 8 weeks, with placebo crossover to 90 mg ustekinumab every 8 weeks. The SLE Responder Index 4 (SRI‐4) at week 24 was used to determine which patients could be classified as ustekinumab responders and which could be classified as nonresponders. In addition to measurements of p40 and IL‐23, serum levels of interferon‐γ (IFNγ), IL‐17A, IL‐17F, and IL‐22, as a proxy for the IL‐12 and IL‐23 pathways, were quantified by immunoassay. Results: Changes in the serum levels of IL‐17A, IL‐17F, and IL‐22 at different time points after treatment were not consistently significantly associated with an SRI‐4 clinical response to ustekinumab in patients with SLE. In contrast, an SRI‐4 response to ustekinumab was significantly associated ( P < 0.01) with durable reductions in the serum IFNγ protein levels at several time points relative to baseline, which was not observed in ustekinumab nonresponders or patients who received placebo. Conclusion: While not diminishing a potential role of IL‐23, these serum biomarker assessments indicate that IL‐12 blockade has an important role in the mechanism of action of ustekinumab treatment in patients with SLE.